My sister in this house - Kesselman, Wendy Ann (N. Doubleday, 1982)
This extraordinary drama, produced to acclaim at the Actors Theatre of Louisville originally, and at NYC's Second Stage, is about a celebrated 1930's French murder case, in which two maids - sisters - were convicted of murdering their employer and her daughter. This very cinematically-structured work explores the motivations which led the sisters to commit murder.